2016
DOI: 10.1161/circulationaha.115.017465
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Diabetes and Offspring Risk of Congenital Heart Disease

Abstract: Background—Maternal diabetes mellitus is associated with an increased risk of offspring congenital heart defects (CHD); however, the causal mechanism is poorly understood. We further investigated this association in a Danish nationwide cohort.Methods and Results—In a national cohort study, we identified 2 025 727 persons born from 1978 to 2011; among them were 7296 (0.36%) persons exposed to maternal pregestational diabetes mellitus. Pregestational diabetes mellitus was identified by using the National Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
219
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(241 citation statements)
references
References 29 publications
18
219
1
3
Order By: Relevance
“…However, in France, experts recommend restricting GDM screening to women presenting with certain risk factors, which could explain the lower prevalence in this study [11]. In a recent large-scale, nationwide Danish cohort, the risk of cardiac malformations was moderately increased in GDM pregnancies [20]. We found similar results, but showed that this increase was significant only in women with insulintreated GDM.…”
Section: Discussionsupporting
confidence: 73%
“…However, in France, experts recommend restricting GDM screening to women presenting with certain risk factors, which could explain the lower prevalence in this study [11]. In a recent large-scale, nationwide Danish cohort, the risk of cardiac malformations was moderately increased in GDM pregnancies [20]. We found similar results, but showed that this increase was significant only in women with insulintreated GDM.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, maternal overweight or unrecognized alterations of glucose metabolism before pregnancy could have contributed to this increased incidence in both groups. Hyperglycemia, altered lipid metabolism and non-enzymatic glycosylation of proteins are responsible of increased oxidative stress and activation of apoptotic cascade, resulting in adverse effects on embryogenesis [3,4,16]. These mechanisms can alter the neural crest cell migration involved in cardiac structural development [17].…”
Section: Discussionmentioning
confidence: 99%
“…Infants of diabetic mothers (IDM) are exposed to an increased risk of structural cardiovascular abnormalities due to multifactorial conditions caused by exposure to prenatal hyperglycemia, alterations of the vascular system and epigenetic mechanisms [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Ассоциация сахарного диабета и ВПС возможна при гипергликемии до 7 нед гестации [4,34]. По резуль-татам исследований последних лет эти данные полностью подтверждаются [35]. При этом установлено, что тип сахарного диабета значения не имеет [35].…”
Section: заболевания беременной женщиныunclassified
“…По резуль-татам исследований последних лет эти данные полностью подтверждаются [35]. При этом установлено, что тип сахарного диабета значения не имеет [35].…”
Section: заболевания беременной женщиныunclassified